Correcting coherent errors with surface codes. (December 2018) - Bravyi, Sergey; Englbrecht, Matthias; König, Robert; Peard, Nolan
Abstract Surface codes are building blocks of quantum computing platforms based on 2D arrays of qubits responsible for detecting and correcting errors. The error suppression achieved by the surface code is usually estimated by simulating toy noise models describing random Pauli errors. However, Pauli noise models fail to capture coherent processes such as systematic unitary errors caused by imperfect control pulses. Here we report the first large-scale simulation of quantum error correction protocols based on the surface code in the presence of coherent noise. We observe that the standard Pauli approximation provides an accurate estimate of the error threshold but underestimates the logical error rate in the sub-threshold regime. We find that for large code size the logical-level noise is well approximated by random Pauli errors even though the physical-level noise is coherent. Our work demonstrates that coherent effects do not significantly change the error correcting threshold of surface codes. This gives more confidence in the viability of the fault-tolerance architecture pursued by several experimental groups. Quantum error correction and coherent noise Coherent effects are shown not to play a significant role in error correction with quantum surface codes. To build a quantum computer, the quantum bit (qubit) has to be protected from external noise and steps have to be taken to detect and correct for errors. Surface codes are a type of quantum code that can correct for such errors. However, the models used to study such codes often fail to capture quantum coherent processes, which could play an important role. By performing large-scale simulations, Robert König from Technical University of Munich and an international team of collaborators show that coherent effects do not significantly impact the error correction in surface codes, giving confidence in the viability of this approach for developing fault-tolerance quantum computing architectures.